IMPROVING READING COMPREHENSION THROUGH KWL STRATEGY - I Gusti Agung Putri Wirastuti; Nengah Dwi Handayani; Ni Wayan Dian Utari (Journal on Studies in English Language Teaching (JOSELT), 2020)
Reading comprehension is a process of transferring information from the writer to the readers. The subjects of the present study had difficulty in identifying general information, specificinformation, textual meaning, and textual reference of reading texts. The objective of the present study was to find out whether or not reading comprehension of the eleventh grade students of SMA (SLUA) Saraswati 1 Denpasar can be improved through KWL Stragey. Therefore, to achieve the objective of the present study, the researcher administered the research instruments : pre-test, post-test and questionnaire. The students’ mean score had improved significantly from the pre-test was 61.63% to 76.35% in cycle I and 81.58 in cycle II. Based on the result in cycle II, the next cycle did not need to be conducted because the researcher expectation achieved in the cycle II. Besides, the result of the questionnaire indicated the students responded the application of KWL strategy in teaching reading comprehension positively. It could be seen that the result of the questionnaire showed the percentage more than 90% agreed on implementation KWL strategy to improve reading comprehension.